The role of interplanetary shock orientation on SC/SI rise time and geoeffectiveness - Selvakumaran, R.; Veenadhari, B.; Ebihara, Y.; Kumar, Sandeep; Prasad, D.S.V.V.D. (My University, 2017)
Interplanetary (IP) shocks interact with the Earth’s magnetosphere, resulting in compression of the magnetosphere which in turn increases the Earth’s magnetic field termed as Sudden commencement/Sudden impulse (SC/SI). Apart from IP shock speed and solar wind dynamic pressure, IP shock orientation angle also plays a major role in deciding the SC rise time. In the present study, the IP shock orientation angle and SC/SI rise time for 179 IP shocks are estimated which occurred during solar cycle 23. More than 50% of the Shock orientations are in the range of 140 –160 . The SC/SI rise time decreases with the increase in the orientation angle and IP shock speed. In this work, the type of IP shocks i.e., Radio loud (RL) and Radio quiet (RQ) are examined in connection with SC/SI rise time. The RL associated IP shock speeds show a better correlation than RQ shocks with SC/SI rise time irrespective of the orientation angle. Magnetic Cloud (MC) associated shocks dominate in producing less rise time when compared to Ejecta (EJ) shocks. Magneto hydrodynamic (MHD) simulations are used for three different IP shock orientation categories to see the importance of orientation angle in determining the geoeffectiveness. Simulations results reveal that shocks hitting parallel to the magnetosphere are more geoeffective as compared to oblique shocks by means of change in magnetic field, pressure and Field Aligned Current (FAC).
Keywords: IP shock orientation; Radio characteristics; SC/SI rise time